Parents’ and caregivers’ experiences and behaviours when eating out with children with a food hypersensitivity - Fiona M. Begen; Julie Barnett; Miriam Barber; Ros Payne; M. Hazel Gowland; Jane S. Lucas (BMC Public Health, 2017)
Abstract Background For parents and caregivers of food hypersensitive (FH) children, accommodating their child’s dietary needs when eating out can be a challenging experience. This study explored caregivers’ experiences and behaviours when eating out with their FH child in order to gain insights into how they support and prepare their child in negotiating safe eating out experiences. Methods A cross-sectional, qualitative design was used. In depth, semi-structured interviews were carried out with 15 caregivers of children with FH. Interviews were analysed using framework analysis. Results Caregivers reported a number of issues relating to eating out with their FH child, or allowing their child to eat out without their supervision. Through themes of ‘family context’, ‘child-focused concerns’, and ‘venue issues’, caregivers described how they managed these and explained the limitations and sacrifices that FH imposed on their child, themselves, and family members. Conclusions Through deeper understanding of the anxieties, negotiations and compromises experienced by caregivers of children with FH when they are eating out, clinicians and support charities can tailor their support to meet the needs of caregivers and children. Support and education provision should focus on providing caregivers of children with FH the tools and strategies to help enable safe eating out experiences.